Togo : Future Sources of Growth - World Bank (World Bank, Washington, DC, 2020)
The objective of this report is to analyze sources of growth in Togo and required reforms in selected sectors (agriculture, manufacturing, transport and logistics, mining, and tourism) to allow the country to accelerate gross domestic product (GDP) growth, therefore creating a basis to move towards reaching the World Bank Group (WBG) twin goals. A first part of the study will provide a macroeconomic analysis of growth in the country as well as cross- cutting constraints in the business environment. The structural trends of the economy were analyzed, concentrating on the performance of key sectors and the main exports. The analysis then explored transversal constraints to growth which typically include investment and operating regulations, including but not limited to the tax burden. Logistics, access to finance or electricity are some of the other issues covered. A second part of this report covered selected sectors that support growth for an in-depth analysis.